2005
DOI: 10.4015/s101623720500010x
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Tissue Engineering

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 75 publications
(74 reference statements)
0
27
0
2
Order By: Relevance
“…112 The scaffold should (1) be biodegradable in a controlled way without cytotoxic, tumorigenetic, nephrotoxic, or other undesirable effects; (2) have a porosity that allows diffusion of nutrients and waste products; (3) support cell viability, proliferation, differentiation, and ECM production; (4) be able to fix to and integrate with the tissue at the defect site; and (5) give mechanical support to the engineered tissue. 104,106 Ideally, as the ECM develops, the scaffold dissolves and disappears. 107 A comparison of chondrocyte cells cultured in rotating bioreactors in Space (Mir Space Station) and on Earth was reported by Freed et al 113 Freed and his team performed experiments with rotating cultures of bovine chondrocytes in polyglycolic acid scaffolds and concluded that after 7 months of cultivating the culture on Earth (static 1 g control) it produced cartilage tissues closer to the natural form than that in Space.…”
Section: Cartilagementioning
confidence: 99%
See 1 more Smart Citation
“…112 The scaffold should (1) be biodegradable in a controlled way without cytotoxic, tumorigenetic, nephrotoxic, or other undesirable effects; (2) have a porosity that allows diffusion of nutrients and waste products; (3) support cell viability, proliferation, differentiation, and ECM production; (4) be able to fix to and integrate with the tissue at the defect site; and (5) give mechanical support to the engineered tissue. 104,106 Ideally, as the ECM develops, the scaffold dissolves and disappears. 107 A comparison of chondrocyte cells cultured in rotating bioreactors in Space (Mir Space Station) and on Earth was reported by Freed et al 113 Freed and his team performed experiments with rotating cultures of bovine chondrocytes in polyglycolic acid scaffolds and concluded that after 7 months of cultivating the culture on Earth (static 1 g control) it produced cartilage tissues closer to the natural form than that in Space.…”
Section: Cartilagementioning
confidence: 99%
“…106,107 Chondrocytes are the most obvious cell source for the tissue engineering of cartilage. 108 However, chondrocyte expansion in a monolayer causes cell dedifferentiation, characterized by decreased proteoglycan synthesis and type II collagen expression, and increased type I collagen expression.…”
Section: Cartilagementioning
confidence: 99%
“…Dissected stifle joints of 4-week-old cadaver piglets were prepared at the Vaccine and Infection Disease Organization (VIDO). For each sample, a full-thickness articular defect (4.5 · 4.5 · 2-2.5 mm depth) was created in the lateral femoral condyle cartilage of the knee, and a scaffold as prepared earlier was then implanted into the created defect area and covered with a piece of periosteum layer, 14 which was concurrently harvested from the proximal femur ( Fig. 2), to mimic the actual surgical procedure used in animal and clinical studies.…”
Section: Sample Preparationmentioning
confidence: 99%
“…As propriedades mecânicas e físico-químicas dos arcabouços utilizados na Engenharia de Tecidos são características importantes, que influenciam a sua aplicação final. Estes arcabouços não só apresentam uma função mecânica, como também apoiam a fixação, migração, proliferação e diferenciação celular para expressão de fenótipos desejáveis [16,19] . As propriedades mecânicas dos arcabouços como a resistência à tração, flexão e compressão, ductilidade (propriedade de suportar a deformação sem romper ou fraturar) e módulo de Young (razão entre tensão e deformação no regime elástico) são determinadas tanto pelas propriedades do material quanto pela estrutura do mesmo (macro, micro e nanoestrutura).…”
Section: Arcabouços Para Cultura De Célulasunclassified
“…Durante a formação, deposição e organização da nova matriz, o ideal é que o arcabouço seja degradado e metabolizado, deixando que o órgão vital ou tecido seja reestabelecido, mantenha ou melhore sua função tecidual [25] . É importante sincronizar o tempo de degradação/absorção do biomaterial com o tempo de regeneração do tecido, possibilitando a transferência gradativa das funções do biomaterial para o tecido recém-formado, não devendo, contudo, originar produtos de degradação que possam interferir com o tecido em crescimento ou originar um processo inflamatório [15,19] . Na escolha do biomaterial, deve-se ter ainda em consideração, que há matrizes cujas características químicas definem a sua suscetibilidade à degradação aquosa ou enzimática [9,15] .…”
Section: Arcabouços Para Cultura De Célulasunclassified